Impact assessment of IEC intervention on knowledge of HIV/AIDS among secondary and higher secondary school students of Himmatnagar, Gujarat, India - Shah, Tejas A.; Brahmbhatt, Nirmal; Pandor, Jyotsna M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Pertaining to increasing incidence of HIV/AIDS among youths, it becomes a need of the hour to make them aware about every aspects of disease. Students of secondary and higher secondary school can be targeted for achieving this goal. The objective of the study was to assess the knowledge about HIV/AIDS among the school students before and after giving educational intervention. Methods: An educational interventional study was carried out among school going adolescents of one of the school situated in the field practice area of one of the rural teaching hospitals of Gujarat. Pre-designed and pre-tested proforma was used for pre and post test study. Educational intervention in the form of power point presentation was conducted on various aspects of HIV/AIDS. Results: Around 163 students participated in the study. Mean age of the students were 16.6±0.7 yrs. Among them, 148 (90.8%) have heard about HIV/AIDS and only 26.3% could tell correctly about full form of HIV/AIDS before intervention. After giving educational intervention this percentage was raised to 89.2% which was significant statistically. Knowledge on almost all the aspects viz. modes of transmission and preventive aspects were significantly raised among the student after giving educational session. Conclusions: Correct knowledge about etiological and preventive aspects were lacking among the students before intervention. Various misconceptions which were prevalent among them were cleared by giving educational intervention. Secondary and Higher secondary schools can be selected as a platform for raising overall awareness about HIV/AIDS.